Insight into the minds of tweens: unlocking the mystery of cool brands / Masdiana Sulaiman - Sulaiman, Masdiana (2013)
This study examines how tweens define cool and why cool brands are important to them. Tweens are essentially the segment between childhood and adolescence or the younger end of the teenagers’ age spectrum and this market is deemed important as their consumption power increases with the growing buying power of consumers specifically in Malaysia. Understanding the definition of cool is important to marketers, but a clear definition of the cool concept has been under-theorized in the field of marketing, psychology or even sociology, particularly with a focus on tweens. To close this gap, this study focuses on how tweens perceived the concept of cool, the importance of the cool notion to them and how this is likely to influence their brand choices. Using the qualitative approach based on the interpretive paradigm with an emic focus, a semi structured interview guide was utilised for the face-to-face interview sessions and through in depth narrative analysis, this study theorizes the cool notion from the perspectives of the tweens who were selected specifically from five primary schools and three secondary schools in Kuala Lumpur, Malaysia. The purposive sampling method used expressed the need to select participants who were deemed able to describe and explain their views on the selection of common goods including apparel, telecommunication gadgets and accessories. Out of the eight participants selected, six were Malays, one Chinese and another Indian, and two of them were boys and the remaining six were girls. The analysis of the study reveals that tweens are well aware of what cool means and are capable of spontaneously defining the concept of cool in their own words. Cool is about popular, trendy, high status, fun, unique, and linked to self-identification. These findings are somewhat dissimilar to previous studies on Generation Y who define cool as functional while tweens in this study define cool as popular. This study also finds clear brand preferences for tweens and their ability to influence directly their parents’ spending which offer enduring insights for practitioners and academic researchers alike. Ultimately, this study establishes a framework for the notion of cool that could be of value to both marketers and researchers. This study concludes with an academic and practical discussion of how the cool concept could be theorised and applied whilst staying in touch with the needs and demands of the tweens’ consumers.